The ADP-Ribosylation Factor 4d Restricts Regulatory T-Cell Induction via Control of IL-2 Availability - Bernd Geers; Julia Hagenstein; Jessica Endig; Hanna Ulrich; Laura Fleig; Paulina Sprezyna; Julita Mikulec; Lukas Heukamp; Gisa Tiegs; Linda Diehl (Cells, 2022)
Interleukin-2 is central to the induction and maintenance of both natural (nTreg) and induced Foxp3-expressing regulatory T cells (iTreg). Thus, signals that modulate IL-2 availability may, in turn, also influence Treg homeostasis. Using global knockout and cell-specific knockout mouse models, we evaluated the role of the small GTPase ADP-ribosylation factor 4d (Arl4d) in regulatory T-cell biology. We show that the expression of Arl4d in T cells restricts both IL-2 production and responsiveness to IL-2, as measured by the phosphorylation of STAT5. Arl4d-deficient CD4 T cells converted more efficiently into Foxp3+ iTreg in vitro in the presence of αCD3ε and TGFβ, which was associated with their enhanced IL-2 secretion. As such, Arl4d−/− CD4 T cells induced significantly less colonic inflammation and lymphocytic infiltration in a model of transfer colitis. Thus, our data reveal a negative regulatory role for Arl4d in CD4 T-cell biology, limiting iTreg conversion via the restriction of IL-2 production, leading to reduced induction of Treg from conventional CD4 T cells.